Java shu ju fen xi zhi nan = Java data analysis / = Java data analysis - Hubbard, J. R. 1943- (Ren min you dian chu ban she = Posts & Telecom Press, 2018)
Detailed summary in vernacular field only.
880-05;"Shu ju wa jue, da shu ju fen xi, NoSQL, shu ju ke shi hua"--Cover. - 880-06;Ben shu you Yingguo Packt Publishing gong si shou quan Ren min you dian chu ban she chu ban
Keywords: Java (Computer program language); Data mining; Information visualization; Electronic data processing; Relational databases; Java (Langage de programmation); Exploration de données (Informatique); Visualisation de l'information; Bases de données relationnelles